1982
DOI: 10.1073/pnas.79.17.5370
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of zinc and other metals to the biological activity of the serum thymic factor.

Abstract: The serum thymic factor (FTS) utilized in its synthetic or natural form loses its biological activity in a rosette assay after treatment with a metal ion-chelating agent, Chelex 100. This activity is restored by the addition of Zn salts and, to a lesser extent, certain other metal salts. FTS activation is secondary to the binding of the metal to the peptide. The metal-to-peptide molar ratio of 1:1 provides the best activation. These data indicate the existence of two forms of FTS. The first one lacks Zn and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
97
0
3

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(102 citation statements)
references
References 12 publications
2
97
0
3
Order By: Relevance
“…Zinc is bound to thymulin in a 1:1 stoichiometry via the side chains of asparagine and the hydroxyl groups of the two serines. Thymulin activity, in vitro and in vivo, in both animals and humans, is dependent on plasma zinc Zinc and immune function M Dardenne concentrations so that marginal changes in zinc intake or availability affect thymulin activity (Dardenne et al, 1982). Thymulin is detectable in the serum of zinc-deficient patients, but is not active.…”
Section: Possible Modes Of Action Of Zinc On the Immune Functionmentioning
confidence: 99%
“…Zinc is bound to thymulin in a 1:1 stoichiometry via the side chains of asparagine and the hydroxyl groups of the two serines. Thymulin activity, in vitro and in vivo, in both animals and humans, is dependent on plasma zinc Zinc and immune function M Dardenne concentrations so that marginal changes in zinc intake or availability affect thymulin activity (Dardenne et al, 1982). Thymulin is detectable in the serum of zinc-deficient patients, but is not active.…”
Section: Possible Modes Of Action Of Zinc On the Immune Functionmentioning
confidence: 99%
“…We used synthetic serum thymic factor (FTS) as a modulator of pancreatic islet cell damage. The physiological function of the thymus-derived serum thymic factor is induction of cell proliferation and stimulation in a manner similar to that of hormones (2,3,11,12,38). A previous report has shown that FTS prevents diabetes induced by alloxan or streptozotocin in rats (53), and in vivo administration of FTS prevents D-variant of Encephalomyocarditis virus-induced diabetes in BALB/cAJcl mice (30).…”
mentioning
confidence: 99%
“…Its exclusive presence in the thymus was initially suggested by its strict thymus dependency and, more recently, by its unique immunohistochemical detection in thymic epithelial cells (TEC) (3)(4)(5). We showed previously that thymulin requires the presence of zinc to express its biological activity (6). The natural peptide completely loses its biological activity (as measured by a rosette inhibition assay) after being incubated with the chelating agent Chelex 100 and is reactivated after treatment with ZnCl2 and, to a lesser extent, other metals-particularly, aluminium and copper.…”
mentioning
confidence: 99%
“…The natural peptide completely loses its biological activity (as measured by a rosette inhibition assay) after being incubated with the chelating agent Chelex 100 and is reactivated after treatment with ZnCl2 and, to a lesser extent, other metals-particularly, aluminium and copper. Although it has not yet been established definitively, much evidence suggests that thymulin incorporates zinc before being secreted by TEC (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation